2022
DOI: 10.26434/chemrxiv-2022-57bg8
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A peripherally located air recirculation device containing an activated carbon filter reduces VOC levels in a simulated operating room

Abstract: Electrosurgery procedures produce airborne contaminants including volatile organic compounds (VOCs). The effectiveness of commercial grade activated carbon at removing toluene, a typical VOC, from the air in an enclosed simulated operating room when interfaced with an air recirculation device was tested. The concentration of toluene in the air was measured using gas sensitive semiconductor VOC sensors. When the air recirculation device containing activated carbon was turned on, the concentration of toluene in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…We previously showed that upon inserting a fresh activated carbon filter, the rate of VOC reduction abruptly increases when toluene, which is a known activated carbon adsorbate, is used as the VOC. 32 During this fourth segment of the experiment, the concentration of formaldehyde in the air decreases by 0.14 ppm, corresponding to an 8% decrease over an approximately 60 min period and is likely a result of diffusion out of the room as suggested above. Regardless of the mechanism, when the coconut carbon is removed and the catalytic foam is inserted into the PNP unit, the formaldehyde levels decrease rapidly and exponentially as shown in Section 5 of Figure 3.…”
Section: ■ Results and Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We previously showed that upon inserting a fresh activated carbon filter, the rate of VOC reduction abruptly increases when toluene, which is a known activated carbon adsorbate, is used as the VOC. 32 During this fourth segment of the experiment, the concentration of formaldehyde in the air decreases by 0.14 ppm, corresponding to an 8% decrease over an approximately 60 min period and is likely a result of diffusion out of the room as suggested above. Regardless of the mechanism, when the coconut carbon is removed and the catalytic foam is inserted into the PNP unit, the formaldehyde levels decrease rapidly and exponentially as shown in Section 5 of Figure 3.…”
Section: ■ Results and Discussionmentioning
confidence: 74%
“…While the activated carbon in the unit might play a role, our previous related efforts show that the rate of formaldehyde removal does not change when comparing an air-purifying system with and without activated carbon. 31 Additionally, our previous work shows that when VOCs are adsorbed to activated carbon, the VOC concentration in the OR air decays in a biexponential manner, 32 unlike the more linear decay shown in phase 3 of Figure 3. Further, upon insertion of a fresh sheet of activated carbon prepared from coconut shell (phase 4), the formaldehyde levels continue their descent at a similar pace compared to the saturated activated carbon filter.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Section 4 of the graph shows that the rate of formaldehyde removal does not change when activated carbon is interfaced with the air recirculating device. While activated carbon has been shown to effectively remove toluene under similar conditions when placed in this same air cleaning device, 10 formaldehyde is more challenging. After monitoring formaldehyde levels for 1 hour with activated carbon inserted into the device, an open cell polyurethane foam containing transition metal oxide catalyst was inserted.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] Inclusion of activated carbon in these devices removes volatile organic compounds (VOCs) from the air. 10 Activated carbon is typically included in surgical smoke evacuation systems to improve the air quality in ORs during electrosurgery. 11,12 However, not all VOCs show the same propensity for binding to the surface of activated carbon.…”
Section: Introductionmentioning
confidence: 99%